Performance of nanofibrillated cellulose with chitosan as a wet-end additive for paper applications - Abdallah, Areej Fathelrahman; Jawaid, Mohammad; Mohamed, Ainun Zuriyati; Md. Tahir, Paridah; Abdullah, Ummi Hani (Elsevier BV, 2023)
The aim of this work is to evaluate of the effect of incorporating nanofibrillated cellulose (NFC) and chitosan (CH) in a dual system as dry additives during papermaking for unbleached bamboo alkaline sulfite anthraquinone methanol (ASAM) under different beating revolutions. Pulp beating at 4000 and 6000 revolutions has comparable properties with varying dosages of NFC (5 and 10) and different chitosan concentrations (0.5, 1, 1.5, and 2). Hand sheets of a basis weight (60 g/cm2) were produced and measured for thickness, tear, tensile, burst index, and resistance to folding under TAPPI standard methods. Results revealed that with an increase in the number of beating revolutions, there was a decrease in the value of freeness. All analyzed pulp had freeness values within the permissible amount of 300–500 mL in papermaking, except 10 NFC, which was 244–190 mL at 6000 revolutions. Furthermore, the addition of chitosan to 1.5 with 5 NFC at 6000 beating revolutions enhanced the tensile index (85.16 Nm/g) and burst index (7.69 kPa. m2/g) in comparison to the sample control. The incorporation of nanofibrillated cellulose and chitosan significantly altered the physical and mechanical strength. Optimal alkaline sulfite anthraquinone methanol ASAM-enhanced paper properties are displayed with 5 NFC and 1.5 chitosan at 6000 beating revolutions.